SELF-ESTEEM REMAJA PADA KELUARGA UTUH DAN TUNGGAL: KAITANNYA DENGAN KOMUNIKASI DAN KELEKATAN ORANG TUA-REMAJA - Hadori, Rachmawati; Hastuti, Dwi; Puspitawati, Herien (Jurnal Ilmu Keluarga dan Konsumen, 2020)
The developmental of self-esteem is very important for adolescents. The high self-esteem refers to ability to predict the success and well-being of adolescents in their adulthood. This study examines the influence of parents-adolescent communication and attachment on adolescents’ self-esteem in intact and single-parent families. This research design was cross-sectional study and was conducted in public and private high schools and vocational schools in Bekasi City. School selection is done purposively. Participants of this study were 200 students who fit with the criteria which are students of class X - XII with an age range of 14-19 years from selected schools in the city of Bekasi from intact and single families. Data analysis wa done by descriptive and inferential analysis (independent t-test and multiple linear regression test). The results showed that family status has a significant influence on adolescent’s self-esteem. Parent-adolescent communication and parent-adolescent attachment have significant positive influence on adolescent’s self-esteem. The implications of research indicates the importance of support and education for families and adolescents to improve self-esteem, especially in adolescents from a single family, for example, changing negative perceptions to positive (feeling yourself useless, worthless to be useful and valuable for others).